The methylome and transcriptome of fetal skin: implications for scarless healing. (October 2016) - Podolak-Popinigis, Justyna; Ronowicz, Anna; Dmochowska, Monika; Jakubiak, Agnieszka; Sachadyn, Paweł
Aim: Fetal skin is known to heal without scarring. In mice, the phenomenon is observed until the 16–17 day of gestation – the day of transition from scarless to normal healing. The study aims to identify key methylome and transcriptome changes following the transition.Materials & methods: Methylome and transcriptome profiles were analyzed in murine dorsal skin using microarray approach.Results & conclusion: The genes associated with inflammatory response and hyaluronate degradation showed increased DNA methylation before the transition, while those involved in embryonic morphogenesis, neuron differentiation and synapse functions did so after. A number of the methylome alterations were retained until adulthood and correlated with gene expression, while the functional associations imply that scarless healing depends on epigenetic regulation.